Navigating the perfect storm: Reflections on the food, energy, and financial crises - Headey, Derek D.; Malaiyandi, Sangeetha; Fan, Shenggen (Wiley, 2010)
The closely interlinked food, energy, and financial crises pose a significant new challenge to the global effort to reduce poverty. In 2008, food prices rose sharply in many countries, and global poverty and hunger levels increased quite markedly. The good news is that the agricultural supply response in many countries was also strong. The impacts of the financial crisis on poor countries have yet to fully roll out, but it is clear that more people have fallen into poverty and more are suffering from hunger. Lastly, there are strong indications that the global food system is fundamentally changing in a number of dimensions. Biofuels are here to stay, and energy and food prices appear to have adjusted to a higher equilibrium and will in turn raise the prospects of renewed volatility in agricultural commodity markets. Trade protection has also resurfaced, but so have renewed investments in agriculture. These fundamental shifts bring with them opportunities and risks that require internationally coordinated responses with strong national buy‐in, as well as timely and relevant research.